The Ablation Properties of CO2 Laser Irradiating to Absorption Media: An In Vitro Study - Sajee Sattayut; Kittiwut Hortong; Chorpaka Kitichaiwan (International Journal of Dentistry)
This study aimed to compare histological affected zone of tissue samples irradiated by defocused CO2 laser at 1, 2, and 3W continuous wave with and without absorption media. The in vitro experiment was conducted in 70 tissue blocks. The samples were randomly allocated into 7 groups: 10 samples each group, namely, the groups irradiated with 1, 2, and 3W, defocused CO2 laser for 5 seconds, the groups irradiated with 1, 2, and 3W, defocused CO2 laser to the absorption media, and the media alone group as a control. Then the samples were stained with Masson’s trichrome and measured the affected borders under light microscope at 10 × 10 magnification. There was no histological alteration in the groups irradiated with the defocused CO2 laser to the absorption media while the groups without using the absorption media showed the tissue alteration by photoablation.